Understanding Students’ Learning Outcomes Differences Through the Application of the Market Place Activity Type of Cooperative Learning Model and the Application of Conventional Learning Models - Evita Evita; Ahmad Syahid; Nurdin Nurdin (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC EDUCATION, 2019)
This study aims to examine the learning outcomes differences through the application of the market place activity type of cooperative learning model and conventional learning models in Islamic Education subjects in Elementary Schools. The method used is quasi-experimental research (a method that has a control class but may not work fully to control the external variables that affect the experiment). The result of the first research indicates that there are differences in the students’ learning outcomes through the application of market place activity type of cooperative learning models and the application of conventional learning models in Islamic Education subjects. This can be seen from the value of sig. (2-tailed) of 0.00 <0.05. Second, there are differences in students’ learning outcomes through the application of market place activity type of cooperative learning models and the application of conventional learning models in Islamic Education subjects at SDN Binangga 1. This can be seen from the value of sig. (2-tailed) of 0.02 <0.05.The third study found differences in learning outcomes of students through the application of market place activity type of cooperative learning models and the application of conventional learning models in Islamic Education subjects at SDN 1 Binangga. This can be seen from the sig. (2-tailed) value of 0.00 <0.05.The implications of this research are expected to be valuable reference and information for educators to be more creative and innovative in implementing learning models so that the material provided will be more easily understood by students.